Fortification of wheat and maize flour with folic acid for population health outcomes (2016)
ABSTRACT: This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the health benefits and safety of folic acid fortification of wheat and maize flour (alone or in combination with other micronutrients) on folate status and health outcomes in the overall population, with emphasis on populations at risk. For the purposes of this review, a fortified wheat product includes any food prepared from fortified wheat flour; a fortified maize flour product includes any food prepared from fortified corn meal or maize flour. We will include composite flours that contain more than 50% wheat or maize within the definition of flour in this review.